Interleukin-12: Functional activities and implications for disease - Zundler, Sebastian; Neurath, Markus (Cytokine & Growth Factor Reviews, 2015)
Interleukin-12 (IL-12) was the first member of the IL-12 family of cytokines to be identified and has therefore become its eponym. It is a heterodimeric protein of two subunits (p35, p40) secreted by phagocytic cells in response to pathogens and mainly acts through STAT4 to induce IFN-? production in T and NK cells. IFN-? in turn mediates proinflammatory functions and activates T-bet. As IL-12 engages in TH1 development, it is believed to represent an important link between innate and adaptive immunity. Following its identification and the finding of its association to TH1 commitment, great hopes were placed in IL-12 to become a target for therapeutic applications in multiple settings of autoimmunity and cancer. Though, the discovery of the related members of the IL-12 family and several rather disappointing attempts to translate experimental results into clinical practice, have relativized these hopes. Nevertheless, IL-12 remains a cytokine of outstanding importance with lots of unresolved questions. In this review, we will first briefly depict the biochemistry of the cytokine, its receptor and the related signal transduction, before summarizing the regulation of IL-12 production and its biological functions. We will then describe the current knowledge about the implication of IL-12 in different murine disease models as well as in the corresponding human conditions and comment on possible consequences for future clinical applications.
EVALuna2:2016